Evaluation of the Effect of Starter Culture on the Quality of White Soft Cheese (Gibna Beyda) - H.A., Mudawi; L.M., Khairalla; A.H., El Tinay (Journal of Veterinary Medicine and Animal Production, 2021)
This investigation was carried out to study the effect of starter culture on the quality of white soft cheese (Gibna Beida), yield and coagulation time. White soft cheese was made from fresh cows milk (heated at 65oC for 30 minutes, then cooled to 35oC), then starter culture was added at different concentrations (1.5, 2.0, 2.5%) in addition to CaCl2 (0.02%), NaCl (2%) and rennet. Chemical analysis, microbial analysis and sensory evaluation were carried out. The coagulation time for cheese made without addition of starter culture (control) was 189 min. and the yield was 9.61%. The obtained results indicated that the use of starter culture at concentration of 2.5% showed reduction in coagulation time to 64 min. and increase in yield to 13.51%. The effect of different concentrations of starter culture on the chemical composition of white soft cheese revealed that the moisture content showed a significant increase from 56.15% to 69.17%, acidity increased from 0.22% to 0.32%, fat content decreased from 27.60% to 21.00%, protein content decreased from 15.00% to 9.40%, total solids decreased from 43.77% to 31.80%. The total bacterial count increased from 2.3 104 to 4.1 106,the yeast count increased from 8.5 104 to 1.7 105. The flavor and overall acceptability were affected by the addition of starter culture. The best flavor and best overall acceptability scores were obtained in cheese made with 1.5% starter culture, while the least score to flavor was obtained in cheese made with 2.5% starter culture